DYNAMIC CAPABILITIES AND INTERNET OF THINGS AS PREDICTORS OF SUPPLY CHAIN PERFORMANCE IN THAILAND: MEDIATING ROLE OF OPERATIONAL AGILITY - Aeknarajindawat, Natnaporn (International Journal of Supply Chain Management, 2019)
Manufacturing sector is largely relying on its supply chain performance to bring efficiency in production in terms of cost and time. Internet of Things (IOT) and Dynamic Data and Information Processing Capabilities (DDIPCs) are found as strong predictors of organizational agility which can probably play part in supply chain performance. Use of IOT and DDIPCs basically enhance flexibility in organizational operations resulting in their smooth functioning. So, this study has tried to analyze the impact of use of IOT and DDIPCs on supply chain performance of manufacturing sector in Thailand in mediating role of organizational agility. Around 67 organizations have been used as sampling frame as data has been collected from their employees through questionnaire-based survey which was subsequently analyzed through SPSS and AMOS by applying tests of CFA and SEM. Hypotheses testing has concluded that both use of IOT and DDIPCs significantly increase supply chain performance through direct and indirect paths. Organizational agility has been also found as significant mediator in respective relationship. Originality in this study lies in association between use of IOT and DDIPCs with supply chain performance which was not tested before. This study has its implications and future research indications too.